First estimates of the contribution of CaCO3 precipitation to the release of CO2 to the atmosphere during young sea ice growth. Issue 1 (29th January 2013) - Geilfus, N.‐X.; Carnat, G.; Dieckmann, G. S.; Halden, N.; Nehrke, G.; Papakyriakou, T.; Tison, J.‐L.; Delille, B.
Abstract: [1] We report measurements of pH, total alkalinity, air‐ice CO2 fluxes (chamber method), and CaCO3 content of frost flowers (FF) and thin landfast sea ice. As the temperature decreases, concentration of solutes in the brine skim increases. Along this gradual concentration process, some salts reach their solubility threshold and start precipitating. The precipitation of ikaite (CaCO3 .6H2 O) was confirmed in the FF and throughout the ice by Raman spectroscopy and X‐ray analysis. The amount of ikaite precipitated was estimated to be 25 µmol kg −1 melted FF, in the FF and is shown to decrease from 19 to 15 µmol kg −1 melted ice in the upper part and at the bottom of the ice, respectively. CO2 release due to precipitation of CaCO3 is estimated to be 50 µmol kg −1 melted samples. The dissolved inorganic carbon (DIC) normalized to a salinity of 10 exhibits significant depletion in the upper layer of the ice and in the FF. This DIC loss is estimated to be 2069 µmol kg −1 melted sample and corresponds to a CO2 release from the ice to the atmosphere ranging from 20 to 40 mmol m −2  d −1 . This estimate is consistent with flux measurements of air‐ice CO2 exchange. Our measurements confirm previous laboratory findings that growing young sea ice acts as a source of CO2 to the atmosphere. CaCO3 precipitation during early ice growth appears to promote the release of CO2 to the atmosphere; however, its contribution to the overall release by newly formed ice is most likely minor. Key Points: First estimate of the release of CO2 by young sea ice in Barrow, Alaska Estimate of the amount of calcium carbonate precipitated as ikaite Role of frost flowers in promoting CaCO3 precipitation and CO2 release